2017
DOI: 10.3389/fimmu.2017.00743
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with the Malaria Diversity-Covering Blood-Stage Vaccine Candidate Plasmodium falciparum Apical Membrane Antigen 1 DiCo in Complex with Its Natural Ligand PfRon2 Does Not Improve the In Vitro Efficacy

Abstract: The blood-stage malaria vaccine candidate Plasmodium falciparum apical membrane antigen 1 (PfAMA1) can induce strong parasite growth-inhibitory antibody responses in animals but has not achieved the anticipated efficacy in clinical trials. Possible explanations in humans are the insufficient potency of the elicited antibody responses, as well as the high degree of sequence polymorphisms found in the field. Several strategies have been developed to improve the cross-strain coverage of PfAMA1-based vaccines, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…A phase Ia/Ib trial was conducted with French and Burkinabe volunteers that reported the induction of antibodies reactive to parasites from different strains [98]. A combination with its natural partner in the invasion process, PfRon2, in an attempt to increase the potency of the IgG antibodies induced has also been tried [99]. However, though this combination was shown to improve the protection conferred by AMA1 alone to P. falciparum infection in Aotus monkeys [100], Ron2 did not improve cross-strain antibodies in humans, nor in vitro growth inhibition [99].…”
Section: The Disease: the Merozoitementioning
confidence: 99%
See 1 more Smart Citation
“…A phase Ia/Ib trial was conducted with French and Burkinabe volunteers that reported the induction of antibodies reactive to parasites from different strains [98]. A combination with its natural partner in the invasion process, PfRon2, in an attempt to increase the potency of the IgG antibodies induced has also been tried [99]. However, though this combination was shown to improve the protection conferred by AMA1 alone to P. falciparum infection in Aotus monkeys [100], Ron2 did not improve cross-strain antibodies in humans, nor in vitro growth inhibition [99].…”
Section: The Disease: the Merozoitementioning
confidence: 99%
“…A combination with its natural partner in the invasion process, PfRon2, in an attempt to increase the potency of the IgG antibodies induced has also been tried [99]. However, though this combination was shown to improve the protection conferred by AMA1 alone to P. falciparum infection in Aotus monkeys [100], Ron2 did not improve cross-strain antibodies in humans, nor in vitro growth inhibition [99]. These data suggest it would be very difficult to cover the worldwide haplotypes in order to confer a global protection against malaria.…”
Section: The Disease: the Merozoitementioning
confidence: 99%
“…AMA1-based vaccines induce strong antibody responses but do not provide significant protection against clinical malaria in controlled infection studies, and their efficacy in field studies is lower than expected 43 , 46 , 57 , 58 . Variations in the dose, adjuvant, and formulation of AMA1-based vaccines showed only moderate improvements 48 , 59 61 . In contrast, rats immunized with the two-component AMA1-RON2L complex elicited higher levels of anti-AMA1 neutralizing antibodies than those immunized with AMA1 alone, likely because the AMA1-RON2L complex better mimics the true AMA1 structure on invading merozoites 62 .…”
Section: Introductionmentioning
confidence: 99%
“…Antibody responses elicited by single AMA1 alleles show significantly lower efficacy against heterologous strains 47 . To address this problem and achieve strain-transcending protection, combinations of up to seven AMA1 alleles or the design of three diversity covering (DiCo) variants to elicit strain-transcending antibody responses were evaluated with limited success 33 , 48 , 51 55 . Malaria antigens also display the immune evasion phenomenon of antigenic diversion, where the action of neutralizing antibodies is prevented by interfering non-neutralizing antibodies that enable parasite survival 56 .…”
Section: Introductionmentioning
confidence: 99%